2016
DOI: 10.1002/2015jd023587
|View full text |Cite
|
Sign up to set email alerts
|

Considering the radiative effects of snow on tropical Pacific Ocean radiative heating profiles in contemporary GCMs using A‐Train observations

Abstract: This study characterizes biases in water vapor, dynamics, shortwave (SW) and longwave (LW) radiative properties in contemporary global climate models (GCMs) against observations over tropical Pacific Ocean. The observations are based on Atmospheric Infrared Sounder for water vapor, CloudSat 2B‐FLXHR‐LIDAR for LW and SW radiative heating profiles, and radiative flux from Clouds and the Earth's Radiant Energy System products. The model radiative heating profiles are adopted from the coupled and uncoupled Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 48 publications
11
54
0
Order By: Relevance
“…atmosphere (TOA). Similarly, a warmer atmosphere produced by increased greenhouse gas concentrations would contain more liquid and less ice, and therefore induce changes in radiation fluxes that would provide a negative feedback to warming [Li andLe Treut, 1992, Senior andMitchell, 1993]. The strength of this feedback, however, depends on the distribution of cloud phase in the present atmosphere, which was, until recently, poorly constrained.…”
Section: Why Should We Care About Cloud Phase?mentioning
confidence: 99%
“…atmosphere (TOA). Similarly, a warmer atmosphere produced by increased greenhouse gas concentrations would contain more liquid and less ice, and therefore induce changes in radiation fluxes that would provide a negative feedback to warming [Li andLe Treut, 1992, Senior andMitchell, 1993]. The strength of this feedback, however, depends on the distribution of cloud phase in the present atmosphere, which was, until recently, poorly constrained.…”
Section: Why Should We Care About Cloud Phase?mentioning
confidence: 99%
“…The radiative effect of falling snow is explicitly considered in CAM5. Some previous studies suggested the paramount importance of the snow radiative effect in reproducing the present-day radiative heating profiles and even polar sea ice in GCM (Li et al, 2016(Li et al, , 2017. Therefore, we repeat all the parameter perturbation experiments for the particle size of falling snow (R es ) in the same way with the those for R ei .…”
Section: Parameter-perturbation Experiments Designmentioning
confidence: 99%
“…Thanks to the steady improvement of model physics and resolution during recent decades, current state‐of‐the‐art coupled general circulation models (CGCMs) are increasingly capable of reproducing the fundamental features of the tropical atmosphere over the Pacific Ocean with fidelity (e.g., AchutaRao & Sperber, ; Dai, ; Flato et al, ; Guilyardi et al, ; Li, Lee, Waliser, David Neelin, et al, ; Li, Lee, Waliser, Stachnik, et al, ; Meehl et al, ; Pincus et al, ; Randall et al, ). However, some biases remain, including an excessive westward extension of the equatorial Pacific cold tongue in most Coupled Model Intercomparison Project phase 3 (CMIP3) and CMIP5 models (e.g., Dai, ; Bernie et al, ; Ham et al, ; Li & Xie, ; Li & Xie, ; Zheng et al, ), with relatively warmer sea surface temperatures (SSTs) on the flanks of the Intertropical Convergence Zone (ITCZ), meaning a weaker zonal SST gradient over the equatorial Pacific (Li, Lee, Waliser, David Neelin, et al, ; Li, Lee, Waliser, Stachnik, et al, ; Li et al, , ; Li & Xie, ; Lin, ; Zhang et al, ). This is linked to weaker surface wind strength and low‐level winds over the trade‐wind regions and an inaccurate precipitation spatial pattern‐the so‐called double ITCZ, with excessive precipitation off the equator, insufficient rainfall over the equatorial Pacific, and an overly zonal orientation of the South‐Pacific Convergence Zone (SPCZ; e.g., Brown et al, ; Li, Lee, Waliser, David Neelin, et al, ; Li & Xie, ; Lin, ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the persistent systematic biases commonly found over the tropical Pacific in most CMIP3 and CMIP5 CGCMs is related to radiative fluxes (Li et al, ; Li, Lee, Waliser, David Neelin, et al, ; Li et al, ; Waliser et al, ). Namely, over convective regions such as the western Pacific warm pool, ITCZ, and SPCZ, there tends to be excessive outgoing longwave radiation (OLR) and underestimated upward shortwave radiation (RSUT) at the top of the atmosphere, with overestimated downward shortwave radiation at the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation